Penerapan P5-PPRA Dalam Pembentukan Karakter Moderasi Beragama dan Kewirausahaan Siswa Madrasah Ibtidaiyah - Ubaidillah; Madinatus Sahara; Jazilatur Rohmah; Nur Rohmatul Wahyuni; Reza Abidatun Ni’mah (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
The implementation of the Pancasila Student Profile and Rahmatan lil Alamin (P5-PPRA) project at the Madrasah Ibtidaiyah level plays a strategic role in shaping students’ religious moderation character and entrepreneurial skills from an early age. This study was motivated by the low implementation of tolerance values and limited entrepreneurship skills among Islamic elementary students in Gresik city, despite the implementation of the Merdeka Curriculum. This research aims to describe the implementation of P5-PPRA, analyze its contribution to forming religious moderation and entrepreneurship, and identify supporting and inhibiting factors. This qualitative case study used observation, interviews, and documentation techniques involving teachers and students of three Islamic elementary schools in Gresik. The results indicate that project-based programs such as entrepreneurship fairs, interfaith tolerance activities, community collaboration, and contextual learning successfully improved students’ understanding of religious moderation and basic entrepreneurial skills. Supporting factors include institutional policy and community involvement, while obstacles arise from teacher competence and time limitations. The study concludes that P5-PPRA is effective in developing students’ religious moderation and entrepreneurship when implemented collaboratively and supported by adequate human resources.